2018
DOI: 10.1016/j.est.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Duty-cycle characterisation of large-format automotive lithium ion pouch cells for high performance vehicle applications

Abstract: A B S T R A C TThe long-term behaviour of lithium ion batteries in high-performance (HP) electric vehicle (EV) applications is not well understood due to a lack of suitable testing cycles and experimental data. As such a generic HP duty cycle (HP-C), representing driving on a race track is validated, and six NMC graphite cells are characterised with respect to cycle-life. To enable a comparison between the HP-EV environment and conventional road driving, two test groups of cells are subject to an experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The overall scheme of the experiment is as follows: taking the battery capacity prediction accuracy, root mean square error and battery life prediction error as the experimental indexes, the proposed method is compared with Kellner et al (2018) and Quiones et al (2018).…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The overall scheme of the experiment is as follows: taking the battery capacity prediction accuracy, root mean square error and battery life prediction error as the experimental indexes, the proposed method is compared with Kellner et al (2018) and Quiones et al (2018).…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The proposed method is compared with the method in Kellner et al (2018) and the method in Quiones et al (2018), and the comparison result is shown in Figure 5. According to Figure 5, it can be seen from the prediction error results in Figure 5 that the prediction error of the proposed method is slightly lower than that of Kellner et al (2018) and Quiones et al (2018), and the minimum prediction error of the proposed method is only 0.013, while the minimum prediction error of Kellner et al (2018) and Quiones et al (2018) is 0.023 and 0.024 respectively.…”
Section: Battery Life Prediction Error Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…e battery life model employed in this research is developed in 2011 and employed by many models recently [20,21]. Although there are newer models [22], the one reported by Wang proposes a formula for battery life assessment.…”
Section: Introductionmentioning
confidence: 99%